2020
DOI: 10.17725/rensit.2020.12.415
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of distribution laws of the phase difference of the envelopes of electromyograms of antagonist muscles in Parkinson's disease and essential tremor patients

Abstract: An investigation of surface electromyogram (EMG) of antagonist muscles in patients with Parkinson's disease (PD) and essential tremor (ET) was carried out. A comparison was made between two methods for calculating instantaneous phases of envelopes of EMG signals. The first method is based on calculating the ridges of wavelet spectrograms of envelopes of EMG signals. The second method is based on using the Hilbert transform. Statistically significant difference between the mean values of the phase difference of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…The method developed for analyzing the wave train electrical activity is a universal method for exploratory data analysis and can be applied to other types of biomedical signals [ 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 ]. In particular, we demonstrated that the statistical analysis of some characteristics of wave trains in EEG can identify features of the preclinical stage of PD [ 58 , 59 , 60 , 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…The method developed for analyzing the wave train electrical activity is a universal method for exploratory data analysis and can be applied to other types of biomedical signals [ 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 ]. In particular, we demonstrated that the statistical analysis of some characteristics of wave trains in EEG can identify features of the preclinical stage of PD [ 58 , 59 , 60 , 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…We applied the method developed earlier for the analysis of the wave train electrical activity [ 42 , 47 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 ] to analyze the local maxima in the cross-wavelet spectra. The method is based on the use of 2D and 3D AUC diagrams.…”
Section: Auc Diagrams Based On Cross-wavelet Spectramentioning
confidence: 99%
“…Phase analysis is widely used in biomedical research [ 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 ]. The Hilbert transform and complex wavelets are usually used for computing the instantaneous phase [ 45 ].…”
Section: Introductionmentioning
confidence: 99%
“…Low-frequency oscillations in trapezius muscle EMG have been suggested as a tool to study neural mechanisms including slow-wave cortical oscillations represented in the descending corticospinal pathways and monoaminergic pathways originating in brain stem reticular formation [33]. Consequently, the 0.5-4 Hz range has revealed neurophysiological regularities in patients with Parkinson's disease [34] suggesting the possibility for improved diagnostic capabilities of cognitive functioning. Additionally, the 6-12 Hz frequency range has been associated with differing parts of the brain, including the cerebellar [35], subcortical [36], sensorimotor cortex [37], and primary motor cortex [38].…”
Section: Introductionmentioning
confidence: 99%